2013
DOI: 10.1007/s10600-013-0440-4
|View full text |Cite
|
Sign up to set email alerts
|

A new isoflavone derivative from Streptomyces sp. YIM GS3536

Abstract: 1 exhibited appreciable cytotoxicity against human melanoma cell lines (B16) and human leukemia cell lines (HL60) with IC 50 values of 17.5 and 19.2 PM, respectively. The MIC values of 1 for Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Candida albicans were in the range of 23-35 PM.Isoflavone intake from soy-based foods reduces the risk factors for cardiovascular disease and hormone-dependent cancers [1][2][3][4]. Streptomycetes are capable of biotransformation of soybean meal as major organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
(18 reference statements)
1
7
0
1
Order By: Relevance
“…The J value (<6 Hz) of the anomer of the sugar moiety indicated the α-orientation at the anomeric center of the d -glucopyranosyl unit. The 13 C NMR data of G1 ( Table S2 ) were in good consistent with those of genistin 43 . In the HMBC spectrum of G1, the anomeric proton signal of glucopyranosyl unit at δ H 6.29 correlated with δ C 164.2, indicating that the glucopyranosyl unit was attached to the hydroxyl of the aglycone C-7.…”
Section: Resultssupporting
confidence: 61%
“…The J value (<6 Hz) of the anomer of the sugar moiety indicated the α-orientation at the anomeric center of the d -glucopyranosyl unit. The 13 C NMR data of G1 ( Table S2 ) were in good consistent with those of genistin 43 . In the HMBC spectrum of G1, the anomeric proton signal of glucopyranosyl unit at δ H 6.29 correlated with δ C 164.2, indicating that the glucopyranosyl unit was attached to the hydroxyl of the aglycone C-7.…”
Section: Resultssupporting
confidence: 61%
“…The dried stems of S. parviflorus were extracted with acetone and the crude extract was separated by column chromatography which led to the isolation of a new 2-arylbenzofuran, spathobenzofuran (1), and ten known compounds; vignafuran (2) (Csékei et al 2008), lyratin B (3) (Zhang et al 2010), (6aR, 11aR)-medicarpin (4) (Yoon et al 2016), phaseollidin (5) (Dagne et al 1993), daidzein (6) (Takeya and Itokawa 1982), formononetine (7) (Granados-Covarrubias and Maldonado 2009), genistein (8) (Huang et al 2013), 3´-methoxydaidzein (9) (Goto et al 2009), 8-O-methylretusin (10) (Mizuno et al 1990) and 7,3´-dihydroxy-8,4´-dimethoxyisoflavone (11) (Puebla et al 2010) as shown in Figure 1. The structures of all isolated compounds were elucidated by spectroscopic methods, especially 1D and 2D NMR spectroscopy, mass spectrometry and physical data.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was discovered in another terrestrial Streptomyces sp. GW39/1530 [28,29]. Furthermore, the molecular formula C9H9NO3 was dereplicated as erbstatin, a simple dehydrotyrosine derivative isolated from Streptomyces amnkusaensis [30,31].…”
Section: Metabolomics Analysis Of the Coculture Extract Of Actinokinementioning
confidence: 99%